An Investigation of Depressive Symptoms in Patients with Congenital Cervical and Vaginal Aplasia: A Cross-Sectional Study - Liu X; Ding J; Li Y; Hua K; Zhang X (Dove Medical Press, 2022)
Xiaotong Liu,* Jingxin Ding,* Yuqi Li, Keqin Hua, Xuyin Zhang Department of Gynecology, Obstetrics and Gynecology, Hospital of Fudan University, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Xuyin Zhang; Keqin Hua, Department of Gynecology, Obstetrics and Gynecology Hospital of Fudan University, 128 Shen yang Road, Shanghai, 200090, People's Republic of China, Tel +86 17355381668 ; +86 19512268803, Email zhangxuyin@163.com; huakeqinjiaoshou@163.comPurpose: Congenital cervical and vaginal aplasia is a rare condition that has a great impact on patients physically and psychologically. The present study was designed to assess depressive symptoms related to congenital cervical vaginal aplasia and provide a scientific basis for formulating psychological intervention measures.Patients and Methods: This was a cross-sectional study of forty-six patients who were diagnosed with congenital cervical and vaginal aplasia and underwent cervicovaginal reconstruction surgery between January 2018 and December 2020. Patients were required to complete a demographic questionnaire, the Patient Health Questionnaire-9 (PHQ-9), the Generalized Anxiety Disorder-7 (GAD-7), and the Symptom Checklist-90 (SCL-90). When patients had sexual activity, their sexual function was evaluated by the Female Sexual Function Index (FSFI) questionnaire. The main outcome was the depressive symptoms screened by PHQ-9, and the factors affecting depressive symptoms were analyzed. Quantitative and categorical variables were compared using Student's t-test and chi-squared test, respectively.Results: Of all patients diagnosed with congenital cervical and vaginal aplasia, 58.7% (27/46) presented moderate to severe depressive symptoms. Some factors were related to the patient's depressive symptoms, such as age, parental attitudes, family disharmony, being teased by peers, sexual dysfunction, fertility anxiety, and feeling uncomfortable while wearing the vaginal mold.Conclusion: Half of patients with congenital cervical and vaginal aplasia have depressive symptoms. These findings stress that psychotherapy should be regarded as an independent treatment for patients with congenital cervical and vaginal aplasia.Keywords: cervicovaginal reconstruction, depression, female genital tract malformation, psychotherapy, PHQ-9